Penentuan Zona Potensial Penangkapan Ikan Berdasarkan Distribusi Suhu Permukaan Laut dan Klorofil-a di Selat Makassar - Berliana, Lia; Anandito, Dinda Niken Zahra; Hidayat, Maitsa' Aulia; Kurniasih, Mirna; Dewi, Vanya Chathy Kemala (PT. Pubsains Nur Cendekia, 2025)
Indonesia as an archipelago with vast marine areas, has a large and diverse fisheries potential and can become one of the leading economic sectors if managed properly. However, the management and utilization of fisheries resources in this country are not optimal because most fishermen and related parties still rely on traditional methods in determining fishing areas. This study aims to map the Zone of Fishing Potential in the Makassar Strait waters using Sea Surface Temperature and chlorophyll-a distribution data for the period May 2024. The results of this study indicate that water areas with suitable chlorophyll-a concentrations (0.2-1.5 mg/m3) combined with optimal sea surface temperatures (between 28°C-30°C) tend to be productive zone of fishing potential. Areas around the coast of Makassar and Polewali Mandar appear to have high potential in supporting such activities.